Lâminas de irrigação por gotejamento na cultura do cafeeiro - Lambert, Ricardo Alexandre (2009)
The purpose of the present work was to evaluate the vegetative development, productivity, yield and income from Rubi´s coffee, inbred MG-1192, cultivated under different irrigation depths during the period of 2002 to 2008. The experiment was carried out at the Glória´s experimental farm, situated at 18º58 South latitude and 48º12 West longitude, and an altitude of approximately 912 m, in Uberlândia, Minas Gerais, Brasil, on a Loamy Dystrophyc Oxysol. The local weather is the Aw type, being dry during winter and warm and rainy during summer. The experimental design was a randomized blocks, with four replicates and eight treatments corresponding to the irrigation depth 0% (without irrigation), 30%, 60%, 90%, 120%, 150%, 180% and 210% according to the class A pan evaporation. The planting was done on January of 2001, with a row spacing of 3,5 m and 0,7 m between plants. The plots were constituted by three rows with eight plants each, being evaluated the four central ones from the middle row. It was utilized the drip irrigation system, with compensating emitters and flow of 3,5 L h-1, with the irrigation being realized every Monday, Wednesday and Friday. Annually, there were measured the coffee plant height, crown diameter, plagiotrophycal spread s length and number of internodes on the ortotrophycal branch. From 2003 on, it was done six consecutive harvest, when there were evaluated the productivity, yield and income. Regarding the coffee plant vegetative development, an average the irrigation depths corresponding to 131,7%, 148,6%, 148,5%, 141,6% and 125,9% of the class A pan, proportionate the higher values for plant height, crown diameter, plagiotrophycal spread s length and internodes number of the ortotrophycal branch respectively. For productivity, yield and income it was not possible to conclude the best irrigation depth. The irrigation did not eliminated the biannually of the production, however, promoted a better vegetative development and productivity when compared to the non irrigated area.